Early postoperative outcomes in a retrospective comparison between Lichtenstein repair method and Rutkow-Robbins repair method for inguinal hernia repair: Zgodnji pooperativni izidi v retrospektivni primerjavi med metodo po Lichtensteinu in Rutkow-Robbins metodi pri operaciji dimeljske kile - Arslani, Nuhi (Acta Medico-Biotechnica, 2025)
Purpose: The purpose of this retrospective study was to determine the difference in postoperative outcomes in inguinal hernia patients treated with a Lichtenstein or Rutkow-Robbins hernioplasty.Methods: Ninety male patients who underwent a Lichtenstein or Rutkow-Robbins hernioplasty were retrospectively analysed. The observed variables were postoperative outcomes, specifically urinary retention, early and late postoperative bleeding, pain and analgesic usage, wound and implant infection, scrotal hematoma and testicular atrophy, patient mobilization time, and hernia recurrence.Results: No statistically significant differences in the incidence of postoperative outcomes were detected between the Lichtenstein and Rutkow-Robbins hernioplasty groups (P > 0.005).Conclusion: No statistically significant differences in postoperative outcomes were detected between patients undergoing Lichtenstein and the Rutkow-Robbins hernioplasty repairs.